2000
DOI: 10.1136/thorax.55.8.650
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects of formoterol and salmeterol: a dose-response comparison in healthy subjects

Abstract: Background-The main adverse eVects of inhaled long acting 2 agonists relate to their systemic activity. The systemic effects seen over eight hours after inhalation of three doses of salmeterol and formoterol were therefore compared in normal subjects. Methods-A double blind, randomised, crossover study was carried out in 16 healthy subjects who inhaled formoterol 24, 48 and 96 µg (via Turbuhaler ® ), salmeterol 100, 200 and 400 µg (via Diskhaler ® ), or placebo on separate days. Heart rate, systolic and diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 29 publications
6
62
2
3
Order By: Relevance
“…Patient overuse of inhaled medications is not uncommon in COPD; patients without COPD who receive and overuse inhaled medications may be at greater risk of dose-dependent adverse eff ects without the benefi t of symptom relief. [28][29][30] Furthermore, studies have shown that as the number of medications increases, medication adherence oft en decreases; thus, the addition of medications that are not indicated may aff ect patient adherence with other necessary medications, further compromising health. 31 Overweight and obese patients could be especially vulnerable to such eff ects because they have more comorbidities, greater use of prescription medications, and higher pharmacy costs than normal weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patient overuse of inhaled medications is not uncommon in COPD; patients without COPD who receive and overuse inhaled medications may be at greater risk of dose-dependent adverse eff ects without the benefi t of symptom relief. [28][29][30] Furthermore, studies have shown that as the number of medications increases, medication adherence oft en decreases; thus, the addition of medications that are not indicated may aff ect patient adherence with other necessary medications, further compromising health. 31 Overweight and obese patients could be especially vulnerable to such eff ects because they have more comorbidities, greater use of prescription medications, and higher pharmacy costs than normal weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…They increase the fine respirable dose fraction by causing impaction of larger particles within the walls of the holding chamber, reduce aerosol velocity and consequently reduce oropharyngeal deposition and local adverse effects. This leads to increased systemic drug absorption from the lung and therefore increased systemic bioavailability which can be measured by using sensitive surrogates of systemic bioactivity [3][4][5][6][7]. The propensity for dose related systemic and local adverse effects with ICS is often dictated by the choice of inhaled steroid, its pharmacokinetic and pharmacodynamic properties, its respirable particle size and site of lung deposition, and type of drug delivery device used.…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary absorption peak observed in all PK studies was within 5 min which indicates that all subjects had performed the were evaluated to estimate relative potency between the two drugs [33]. Relative potency was adequately estimated in this study as both drugs had dose-related effects on the systemic parameters.…”
Section: Discussionmentioning
confidence: 81%
“…The ratio of doses giving equivalent effects (potency ratio) indicates relative potency of two formulations [32,33]. In a previous study, three doses of formoterol (24,48, and 96 µg) and salmeterol (100, 200 and 400 µg)…”
Section: Pk Parameters Test (T) Reference (R) % (T/r)*mentioning
confidence: 99%